Forensic Signatures of Nuclear Materials Processing - Thompson, Nathan (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.The field of nuclear forensics has been noted of relevance in the effort to tackle illicit trafficking of nuclear material.1 Forensic signatures can be considered a 'fingerprint' of the material, obtained by analytical methods such as X-Ray diffraction spectroscopy (XRD) and scanning electron microscopy (SEM). The forensic signatures obtained from characterising nuclear material may help to determine the origin and processing conditions of the sample. The aim of this project is to investigate how the physical and chemical characteristics of UO3 powder produced from aqueous reprocessing are affected by the processing route, conditions and impurities present. This will be used to develop a library of characteristic forensic signatures to aid in the discrimination of material from different sources.To date, work in this project has included the investigation of forensic signatures of studtite calcination products, whereby calcination products up to 1050 ˚C were characterised. Additionally, a screening investigation into the effect of a matrix of processing variables on UO3 signatures (from studtite intermediate) has been conducted.
Keywords: 'Uranium'; 'Decomposition'; 'Signatures'; 'DSDS17'; 'DSDS17 poster'; 'Forensic Chemistry'